Our shared stake - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2009)
It's the time of the active citizen. Recent spurts of collective campaigning have mobilised surprising ground support. Eugene Tan analyses the coming age of civil society here through the passionate and visible advocacy of certain groups in recent events.